2000
DOI: 10.1034/j.1600-0773.2000.pto870208.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Trigger Function of Valproic Acid in Xenobiotic‐Induced Hepatotoxicity

Abstract: The influence of the antiepileptic drug, valproic acid (2-n-propylpentanoic acid), on the hepatocellular capacity, to cope with an extrinsic oxidative stress was investigated. Freshly isolated rat hepatocytes exposed to therapeutic concentrations of valproic acid (0.25-1.0 mmol/l) were less resistant than controls, as evidenced by a significant cytotoxic response after challenge of the cells with a non-toxic dose of allyl alcohol (2-propen-1-ol). Valproic acid alone was not toxic to hepatocytes even at ten tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…A growing body of evidence suggests increased levels of free radicals following treatment with VPA. A possible VPA biotransformation and/or alterations in natural antioxidants (Graf et al, '98;Klee et al, 2000;Bykov et al, 2004) may contribute to the VPA-associated complications. Antioxidants are, however, the primary candidates to counteract such toxic effect.…”
mentioning
confidence: 99%
“…A growing body of evidence suggests increased levels of free radicals following treatment with VPA. A possible VPA biotransformation and/or alterations in natural antioxidants (Graf et al, '98;Klee et al, 2000;Bykov et al, 2004) may contribute to the VPA-associated complications. Antioxidants are, however, the primary candidates to counteract such toxic effect.…”
mentioning
confidence: 99%
“…Valproic acid was shown to affect hepatocellular defense mechanisms against extrinsic oxidative stress and to produce oxidative stress itself. [55][56][57] In addition, it was suggested that a predisposition of hepatocytes to oxidative stress may play a role in the fatal hepatotoxicity of valproic acid. 55 Although its exact mechanism of action remains to be elucidated (that is, hepatic damage as a consequence of the higher exposure to 'free' SN-38 of valproic acid preexposed hepatocytes or the other way around), it seems that combining fully dosed irinotecan therapy with valproic acid may result in severe hepatotoxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Sodium valproate chronic therapy or Sodium valproate overdose produces L-carnitine (LCAR) depletion and this could impair β-oxidation leading to increase in ω-oxidation pathway and further the formation of toxic metabolites leads to mucocutaneous reaction. Moreover, impairment of β-oxidation leads to hyper ammonemia which is the major cause of seizures; so, combination therapy with Lcarnitine is recommended [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%